Buddhist saints in India : a study in Buddhist values and orientations - Ray, Reginald A. (Oxford University Press, 1999)
The issue of saints is a difficult and complicated problem in Buddhology. In this magisterial work, Ray offers the first comprehensive examination of the figure of the Buddhist saint in a wide range of Indian Buddhist evidence. Drawing on an extensive variety of sources, Ray seeks to identify the "classical type" of the Buddhist saint, as it provides the presupposition for, and informs, the different major Buddhist saintly types and subtypes. Discussing the nature, dynamics, and history of Buddhist hagiography, he surveys the ascetic codes, conventions and traditions of Buddhist saints, and the cults both of living saints and of those who have "passed beyond." Ray traces the role of the saints in Indian Buddhist history, examining the beginnings of Buddhism and the origin of Mahayana Buddhism.